Clinical Perspectives on Targeting of Myeloid Derived Suppressor Cells in the Treatment of Cancer - Najjar, Yana G.; Finke, James H. (Frontiers in Oncology, 2013)
Tumors escape immune recognition by several mechanisms, and induction of myeloid derived suppressor cells (MDSC) is thought to play a major role in tumor mediated immune evasion. MDSC arise from myeloid progenitor cells that do not differentiate into mature dendritic cells, granulocytes, or macrophages, and are characterized by the ability to suppress T cell and natural killer cell function. They are increased in patients with cancer including renal cell carcinoma (RCC), and their levels have been shown to correlate with prognosis and overall survival. Multiple methods of inhibiting MDSCs are currently under investigation. These can broadly be categorized into methods that (a) promote differentiation of MDSC into mature, non-suppressive cells (all trans retinoic acid, vitamin D), (b) decrease MDSC levels (sunitinib, gemcitabine, 5-FU, CDDO-Me), or (c) functionally inhibit MDSC (PDE-5 inhibitors, cyclooxygenase 2 inhibitors). Recently, several pre-clinical tumor models of combination therapy involving sunitinib plus vaccines and/or adoptive therapy have shown promise in MDSC inhibition and improved outcomes in the tumor bearing host. Current clinical trials are underway in RCC patients to assess not only the impact on clinical outcome, but how this combination can enhance anti-tumor immunity and reduce immune suppression. Decreasing immune suppression by MDSC in the cancer host may improve outcomes and prolong survival in this patient population.